Metabolites able to predict uterine diseases in crossbred dairy cows during the transition period - Erick Daibert; Paula Batista de Alvarenga; Amanda Lima Rezende; Nádia Simarro Fagundes; Barbara Cristina Krüger; Ricarda Maria dos Santos; Antonio Vicente Mundim; João Paulo Elsen Saut (Semina: Ciências Agrárias, 2018)
This study aimed to identify possible metabolites able to predict puerperal uterine diseases in crossbred dairy cows (Holstein x Gir) in the transition period. We hypothesized that, as what has been observed for Holstein cows, a negative energy balance (NEB) may increase the incidence of uterine diseases. Thirty-four lactating crossbred cows (½HG, ¼HG, ¾HG, and 5/8HG) were evaluated during prepartum (-60d and -30d), calving, and postpartum (+14d, +21d, and +35d) periods, being divided into two groups (with and without uterine diseases). NEB evaluations were based on the concentrations of non-esterified fatty acids (NEFA) and beta-hydroxybutyrate (BHBA) at calving and 14 days postpartum. Nearly 1/3 of the crossbred cows presented an NEB, characterized by a significant increase in NEFA with no BHBA increase; however, it was less intense than that observed in Holstein cows during the transition period. There was a significant difference between cows with and without uterine diseases in NEFA and calcium concentrations at partum, as well as body condition score (BCS) during prepartum. In conclusion, the occurrence of uterine diseases during the transitional period is related to the BCS in the prepartum period, besides serum NEFA and calcium concentrations at partum.